House, but no garden : apartment living in Bombay's suburbs, 1898-1964 - Rao, Nikhil (University of Minnesota Press, 2013)
Between the well-documented development of colonial Bombay and sprawling contemporary Mumbai, a profound shift in the city's fabric occurred: the emergence of the first suburbs and their distinctive pattern of apartment living. This book considers this phenomenon and its significance for South Asian urban life. It explores the organisation of the middle-class neighbourhood which became ubiquitous in the mid twentieth century city and which has spread throughout the subcontinent.